ANALISIS PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BAN MAXXIS MELALUI MINAT BELI PADA CV HARKAT FAWWAZ SEJAHTERA - Dhimas Putra Nugroho; Abu Bakar (CV. Adiba Aisha Amira, 2024)
This research aims to determine the influence of product quality, brand image and price on purchasing decisions for Maxxis tires through purchase interest as an intervening variable at CV Harkat Fawwaz Sejahtera. The sampling technique used was random sampling with a sample size of 100 respondents. The data was analyzed using SPSS version 25 software. Based on the research results, it shows that product quality and brand image have no influence on purchasing decisions, while price and buying interest influence purchasing decisions. However, the purchase interest variable was not able to mediate the influence of the product quality, brand image and price variables on the decision to purchase Maxxis tires at CV Harkat Fawwaz Sejahtera.